Презумпция невиновности: Записки прокурора / А. А. Безуглов - Безуглов А. А. (Новинки " Современника ", 1985)
Экземпляры: б/ф-2 (20100617) / Инвентарный номер: 8245 / Цена: 1.60 / Авт.знак: Б 40 / ББК: 84 (2Рос=Рус)6